Clinical features of COVID-19-related optic neuritis: a retrospective study - Zhao, Fang-Fang; Wang, Yun; Li, Tai-Ping; Hu, Shuan; Yu, Xin-Sheng; Li, Xinxin; Cen, Jingyun; Huang, Kefan; Lin, Hongjie; Yang, Jian-Feng; Chen, Lan; Cen, Ling-Ping (Frontiers in Neurology, 2024)
Objective This retrospective study aimed to investigate the clinical features of optic neuritis associated with COVID-19 (COVID-19 ON), comparing them with neuromyelitis optica-associated optic neuritis (NMO-ON), myelin oligodendrocyte glycoprotein-associated optic neuritis (MOG-ON), and antibody-negative optic neuritis (antibody-negative ON). Methods Data from 117 patients (145 eyes) with optic neuritis at the Shantou International Eye Center (March 2020–June 2023) were categorized into four groups based on etiology: Group 1 (neuromyelitis optica-related optic neuritis, NMO-ON), Group 2 (myelin oligodendrocyte glycoprotein optic neuritis, MOG-ON), Group 3 (antibody-negative optic neuritis, antibody-negative ON), and Group 4 (optic neuritis associated with COVID-19, COVID-19 ON). Characteristics of T2 and enhancement in orbital magnetic resonance imaging (MRI) were assessed. Best-corrected visual acuity (BCVA) was compared before treatment, at a short-term follow-up (14 days), and at the last follow-up after treatment. Results The COVID-19-associated optic neuritis (COVID-19 ON) group exhibited 100% bilateral involvement, significantly surpassing other groups (P < 0.001). Optic disk edema was observed in 100% of COVID-19 ON cases, markedly differing from neuromyelitis optica-related optic neuritis (NMO-ON) (P = 0.023). Orbital magnetic resonance imaging (MRI) revealed distinctive long-segment lesions without intracranial involvement in T1-enhanced sequences for the COVID-19 ON group compared to the other three groups (P < 0.001). Discrepancies in optic nerve sheath involvement were noted between the COVID-19 ON group and both NMO-ON and antibody-negative optic neuritis (antibody-negative ON) groups (P = 0.028). Before treatment, no significant difference in best-corrected visual acuity (BCVA) existed between the COVID-19 ON group and other groups. At the 14-day follow-up, BCVA in the COVID-19 ON group outperformed the NMO-ON (P < 0.001) and antibody-negative ON (P = 0.028) groups, with no significant difference observed compared to the myelin oligodendrocyte glycoprotein optic neuritis (MOG-ON) group. At the last follow-up after treatment, BCVA in the COVID-19 ON group significantly differed from the NMO-ON group (P < 0.001). Conclusion Optic neuritis associated with COVID-19 (COVID-19 ON) predominantly presents with bilateral onset and optic disk edema. Orbital magnetic resonance imaging (MRI) demonstrates that COVID-19 ON presents as long-segment enhancement without the involvement of the intracranial segment of the optic nerve in T1-enhanced images. Glucocorticoid therapy showed positive outcomes.